The Use of Extracellular Vesicles as a Promising Therapeutic Approach for Pulmonary Diseases - Sirous Sadeghian Chaleshtori; Zanyar Pirkani; Massoumeh Jabbari Fakhr; Mona Mokhber (Health Science Reports)
ABSTRACT Background and Aims Pulmonary disorders significantly impact worldwide healthcare, highlighting the necessity for enhanced diagnostic and treatment approaches. This narrative review seeks to investigate the potential of extracellular vesicles (EVs) as an innovative therapeutic strategy for diverse pulmonary disorders. Methods This review synthesizes existing data about the function of extracellular vesicles (EVs) in pulmonary health and pathology, emphasizing their modes of action, including the transfer of proteins, nucleic acids, and lipids for intercellular communication. It also examines the implications of EVs in targeted medication delivery, immunomodulation, and tissue regeneration. Results EVs, including microvesicles and exosomes, have demonstrated promise in treating respiratory diseases such as chronic obstructive pulmonary disease (COPD), asthma, pulmonary fibrosis, and acute respiratory distress syndrome (ARDS). Additionally, EVs may serve as valuable biomarkers for early disease detection, prognosis, and monitoring. However, challenges remain regarding the standardization of EV isolation methods and characterization protocols to ensure safety and clinical applicability. Conclusion In summary, extracellular vesicles hold potential for transforming the management of pulmonary diseases by providing insights into pathophysiology, enabling early diagnosis, and facilitating personalized treatment approaches. Further exploration of EV‐based therapies is necessary to fully realize their potential in improving outcomes for lung disorders.